Ovulatory Follicular Dynamics After Estrus Synchronization using Prostaglandin F2a in Dairy Cows - Prabowo Purwono Putro; Asmarani Kusumawati (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
The study aimed to follow development of ovulatory follicular dynamics as well as plasma progesterone profile after estrus synchronization using PGF2 and GnRH. A total of 15 non-pregnant dairy cows, 4-5 years of age, healthy and reproductively sound were used in the present study. Treatment 1, given intramuscular injection of PGF2 25 mg (PGF2), treatment 2 PGF2 25 mg and GnRH 250 g 2 days later (PGF2-GnRH), and treatment 3 with GnRH 250 g (7 days prior to injection of PGF2), PGF2 25 mg and GnRH 250 g (2 days after injection of PGF2) (GnRH-PGF2a-GnRH) (the Ovsynch method). Transrectal ultrasonographic examination using real time, B-mode, with 7.5 MHz tranducer was performed everyday for 12 days to follow ovulatory follicular and luteal dynamics. Blood plasma was taken every day for progesterone determination using EIA technique. Data of follicular, luteal development and progesterone levels were tested using analysis of variance and correlation analysis. The animals showed estrus within 70.70 + 01.90 hours following PGF2 injection. Prostaglandin F2 induced corpus luteum regression, decreased in progesterone plasma levels, followed by ovulatory follicular development and eventually underwent ovulation. Administration of first GnRH increased corpus luteum size, enhanced its regression and decreased plasma progesterone levels, while the second administration induce better ovulatory follicular development. Rate of the corpus luteum regression, progesterone decrease and ovulatory follicular development following PGF2 injection for respective treatments 1, 2 and 3 were 2.53 + 0.24a, 2.73 + 0.36a and 3.53 + 0.28b mm/day; 1.39 + 0.14a, 1.35 + 0.18a dan 1.57 + 0.12b ng/ml/day; and 1.33 + 0.15a, 1.63 + 0.19b and 1.67 + 0.23b mm/day, respectively (P < 0.05). It can be concluded that PGF2 induced corpus luteum regression, decreased in progesterone plasma levels and ovulatory follicular development. Addition of GnRH increased corpus luteum size and plasma progesterone levels, after PGF2 injection corpus luteum regression and progesterone decrease became more prominent, while ovulatory folliculkar development occurred much better. .